Karl Polanyi on issues of war and peace - Maciej Kassner (economic sociology. perspectives and conversations, 2023)
The Russian full-scale invasion of Ukraine, which started in February 2022, forcefully brought war to the forefront of public and scholarly debates. In this essay, I propose to address the topic of war through the examination of Karl Polanyi's political writings. At first sight, it may seem to be an odd choice. Admittedly, Polanyi's writings concerning war are scattered and relatively obscure. There are, however, at least two reasons to engage in such inquiry.
Keywords: 300